# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime \prime }+5 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-7 y^{\prime }+10 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }-24 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-25 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}3 y^{\prime \prime }+7 y^{\prime }-6 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-8 y^{\prime }+15 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-8 y^{\prime }+15 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-8 y^{\prime }+15 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-9 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-9 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-9 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-10 y^{\prime }+25 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }-4 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}25 y^{\prime \prime }-10 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}16 y^{\prime \prime }-24 y^{\prime }+9 y = 0
\] |
✓ |
✓ |
|
\[
{}9 y^{\prime \prime }+12 y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-8 y^{\prime }+16 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-8 y^{\prime }+16 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-8 y^{\prime }+16 y = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }+4 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }+4 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }+4 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+25 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+5 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+5 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+29 y = 0
\] |
✓ |
✓ |
|
\[
{}9 y^{\prime \prime }+18 y^{\prime }+10 y = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+16 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+16 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+16 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+13 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+13 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+13 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }+\left (\frac {1}{4}+4 \pi ^{2}\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }+\left (\frac {1}{4}+4 \pi ^{2}\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-5 x y^{\prime }+8 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-2 x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }-x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-5 x y^{\prime }+9 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+5 x y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}4 x^{2} y^{\prime \prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-19 x y^{\prime }+100 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-5 x y^{\prime }+29 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-x y^{\prime }+10 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+5 x y^{\prime }+29 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }+5 x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}4 x^{2} y^{\prime \prime }+37 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }-25 y = 0
\] |
✓ |
✓ |
|
\[
{}4 x^{2} y^{\prime \prime }+8 x y^{\prime }+5 y = 0
\] |
✓ |
✓ |
|
\[
{}3 x^{2} y^{\prime \prime }-7 x y^{\prime }+3 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-2 x y^{\prime }-10 y = 0
\] |
✓ |
✓ |
|
\[
{}4 x^{2} y^{\prime \prime }+4 x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-11 x y^{\prime }+36 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-x y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-3 x y^{\prime }+13 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = 24 \,{\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = 24 \,{\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }-8 y = 8 x^{2}-3
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }-8 y = 8 x^{2}-3
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-9 y = 36
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-3 y^{\prime }-10 y = -6 \,{\mathrm e}^{4 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-3 y^{\prime }-10 y = 7 \,{\mathrm e}^{5 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+6 y^{\prime }+9 y = 169 \sin \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-4 x y^{\prime }+6 y = 10 x +12
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-3 y^{\prime }-10 y = {\mathrm e}^{4 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-3 y^{\prime }-10 y = {\mathrm e}^{5 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-3 y^{\prime }-10 y = -18 \,{\mathrm e}^{4 x}+14 \,{\mathrm e}^{5 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-3 y^{\prime }-10 y = 35 \,{\mathrm e}^{5 x}+12 \,{\mathrm e}^{4 x}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-4 x y^{\prime }+6 y = 1
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-4 x y^{\prime }+6 y = x
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-4 x y^{\prime }+6 y = 22 x +24
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-7 x y^{\prime }+15 y = x^{2}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-7 x y^{\prime }+15 y = x
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-7 x y^{\prime }+15 y = 1
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-7 x y^{\prime }+15 y = 4 x^{2}+2 x +3
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+9 y = 52 \,{\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-6 y^{\prime }+9 y = 27 \,{\mathrm e}^{6 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }-5 y = 30 \,{\mathrm e}^{-4 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime } = {\mathrm e}^{\frac {x}{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-3 y^{\prime }-10 y = -5 \,{\mathrm e}^{3 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+9 y = 10 \cos \left (2 x \right )+15 \sin \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-6 y^{\prime }+9 y = 25 \sin \left (6 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime } = 26 \cos \left (\frac {x}{3}\right )-12 \sin \left (\frac {x}{3}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }-5 y = \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-3 y^{\prime }-10 y = -4 \cos \left (x \right )+7 \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-3 y^{\prime }-10 y = -200
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }-5 y = x^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-6 y^{\prime }+9 y = 18 x^{2}+3 x +4
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+9 y = 9 x^{4}-9
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+9 y = x^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+9 y = 25 x \cos \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-6 y^{\prime }+9 y = \sin \left (x \right ) {\mathrm e}^{2 x}
\] |
✓ |
✓ |
|